2012
DOI: 10.1016/j.jmii.2011.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Non-typhoidal Salmonella bacteremia among adults: An adverse prognosis in patients with malignancy

Abstract: Malignancy is an adverse prognostic factor in patients with NTS bacteremia. Food safety in patients with malignancy should be emphasized to prevent salmonellosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 23 publications
2
28
1
3
Order By: Relevance
“…30 However, another recent study in Taiwan showed an increasing proportion of serogroup D and a decreasing proportion of S. choleraesuis during a 10-year observation period. 8 S. choleraesuis has decreased in recent years, although it has been reported as a cause of invasive extraintestinal infections in the elderly, especially mycotic aneurysm. 31 In Taiwan, S. choleraesuis is also associated with greater antibiotic resistance, compared to serogroups B or D isolates.…”
Section: Discussionmentioning
confidence: 99%
“…30 However, another recent study in Taiwan showed an increasing proportion of serogroup D and a decreasing proportion of S. choleraesuis during a 10-year observation period. 8 S. choleraesuis has decreased in recent years, although it has been reported as a cause of invasive extraintestinal infections in the elderly, especially mycotic aneurysm. 31 In Taiwan, S. choleraesuis is also associated with greater antibiotic resistance, compared to serogroups B or D isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst the foodborne pathogens, Salmonella and Staphylococcus aureus (S. aureus) are the most common and frequent pathogens responsible for food poisoning and food related infections [4,5] . Salmonella enterica is a leading cause of enteric diseases in human and animal with millions of illness worldwide, whereas the nontyphoidal Salmonella species as a zoonotic agent are also predominantly associated with foodborne infections [2,6,7] . Salmonella species in foods of animal origin are most frequently considered to be associated with the foodborne pathogen outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…While passive processes are apparently responsible for Salmonella accumulation in tumors [8], lipopolysaccharide (LPS) can still cause sepsis and endotoxic shock during bacterial migration to the tumor [9]. LPS causes sepsis by activating Toll-like receptors that promote the hyperinflammatory and vasodilatory effects underlying endotoxic shock [10].…”
Section: Manipulations To Salmonella and Control Measures That Obviatmentioning
confidence: 99%